Impact of Thermal Modification on Swelling and Mechanical Behavior of Couratari spp. - Andrade, Fernando Wallase Carvalho [UNESP]; Moutinho, Victor Hugo Pereira; Severo, Elias Taylor Durgante [UNESP]; da Silva Ferreira, Jessica Sabrina; Ballarin, Adriano Wagner [UNESP] (My University, 2023)
Thermal modification mechanisms and their effects on physical and mechanical properties of native Amazon hardwoods are not yet completely understood. It is expected that such treatments can improve the properties of low-value Amazonian woods and sapwood residues. This study aimed to investigate the impact of heat treatment on the swelling and mechanical properties (strength and stiffness to Static Bending and Janka hardness) of tauari wood (Couratari spp.), a low-value Amazonian hardwood. For this, tauari wood samples were thermally modified in an electric oven under hot air irradiation at final temperatures of 160 °C, 170 °C, 180 °C, 190 °C, 200 °C, and 210 °C for 2.5 h. The main results showed that thermal modification increased the hydrophobicity of tauari wood without any noticeable effects on the mechanical behavior of the wood up to 200 °C. It was stated that up to 200 °C thermal modification is beneficial in terms of gains in hydrophobicity. In contrast, above 200 °C, despite an increase in hydrophobicity, consistent decreases in strength (MOR) and hardness were observed.
Keywords: Amazon wood; MOR; Swelling coefficients; Thermally modified wood